Digital Payment and Financial Technology: Their Impact on the Financial Performance of MSMEs in Yogyakarta - Eska Prima Monique Damarsiwi; Andriyani Prawitasari; Nia Indriasari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
Digital transformation has driven significant changes in the business activities of MSMEs, particularly in the areas of transactions and financial management. The use of digital payments and financial technology (FinTech) is one strategy that can improve operational efficiency, expand access to financial services, and support improved business performance. This study aims to analyse the impact of digital payments and financial technology on the financial performance of MSMEs in the Special Region of Yogyakarta. The study employs a quantitative approach using explanatory research methodology. Data were collected through the distribution of questionnaires to 200 MSME operators selected using purposive sampling. The Digital Payment variable was measured using indicators of QRIS usage, e-wallet usage, ease of transactions, transaction speed, transaction security, and ease of transaction recording. The Financial Technology variable was measured using indicators of ease of access to digital financial services, ease of obtaining digital financing, efficiency of business financial management, and ease of monitoring transactions and cash flow. Meanwhile, Financial Performance was measured through sales growth, profit growth, operational cost efficiency, improved cash flow, and increased profitability. Data analysis was carried out using multiple linear regression with the aid of SPSS software. The results of the study indicate that Digital Payment has a positive and significant effect on Financial Performance.